The Effectiveness of the Touch Math Program in Teaching Addition ‎to Students with Math Disability - Al-Hmouz ‎, Hanan (Jordan Journal of Educational Sciences, 2018)
The purpose of this study was to investigate the effectiveness of the Touch Math program, and the Math Curriculum Based Measurements (M-CBM) on mastering the basic addition facts for third grade students with Math Disability (MD). A total sample of 44 third grade students participated in the study. This study presents a comparison of two groups: The Touch Math and M-CBM group, and the Touch Math group. The intervention was implemented for 16 weeks. The findings indicated that both groups of the study achieved higher scores in math achievement as a result of applying Touch Math program, but Touch Math program and M-CBM had better results compared to just Touch Math program on students' performances during the intervention and follow-up phases. In addition, participants developed a positive increase/trend-line in their M-CBM addition skills because of using.